Monitoring of probiotic bacterial cells Lactobacillus casei in dry fermented sausages - Radka Burdychová; P. Hoferková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
Combination of microbiology cultivation methods and methods of molecular biology is the best way how to achieve correct qualitative and quantitative probiotic analysis. The aim of this study was monitoring of amounts of different starter bacteria supplemented with probiotic bacterial cells Lactobacillus casei (Chr. Hansen) during fermentation and ripening of fermented sausages. Two starter cultures, one consisted of Pediococcus pentosaceus and Staphylococcus xylosus, the second of Pediococcus pentosaceus and Staphylococcus carnosus, were used for the production of sausages. As a detection method of starter and probiotic cell counts, the cultivation on MRS –IM – sorbitol agar was used. Furthermore, the confirmation of L. casei was carried out using species specific PCR. The counts of probiotic L. casei in both probiotic sausages were 106/g and stayed at this level during the whole ripening period (100 days). The counts of starter bacteria were 107/g after the 7 days of fermentation and stayed at this level during the whole fermentation period. PCR from one bacterial colony confirmed the identity of L. casei in 80% of analysed colonies.